Upaya Peningkatan Prestasi Belajar Matematika Materi Statistika dan Peluang Menggunakan Metode Resitasi pada Siswa Kelas IX-D SMP Negeri 1 Grogol Kabupaten Kediri - Sujoko, Nanang Andi (Universitas Nusantara PGRI Kediri, 2023)
The purpose of this research is to improve mathematics learning achievement in statistics material and opportunities using recitation methods or giving assignments. This action research was conducted at Grogol 1 Public Middle School, Kediri Regency by taking research subjects for Class IX-D Grogol 1 Public Middle School, Kediri Regency, Even Semester 2017/2018 Academic Year, Mathematics subject, Statistics and Opportunity Material. Based on the results of the analysis from this classroom action research, it can be concluded as follows: 1) Learning with the Recitation method can increase student learning activities. This can be seen from the results of the analysis of learning activities which show that in cycle 1 students who joked there were 19 students or 52.78%, students who paid attention to 17 students or 47.22%, students who actively thought there were 15 students or 41.67, active students in group activities there are 18 students or 50%. 2) In cycle 2 there are 7 students or 19.44% of students who joke around, students who pay attention to 29 students or 80.55%, students who actively think there are 27 students or 75%, students who are active in group activities there are 30 students or 83, 33%. 3) The Recitation Method can improve Mathematics Learning Achievement in Statistics Materials and Opportunities in Class IX-D Students of SMP Negeri 1 Grogol, Kediri Regency, Even Semester in the 2017/2018 Academic Year. This can be seen from the increase in student achievement as indicated by the increase in the average class score in cycle 1 of 74.61 increasing to 81.5 in cycle 2. The increase in class average was also followed by an increase in the percentage of classical completeness in cycle 1 of 75% increased to 88.89% in cycle 2.